The Effectiveness of The Revolving Fund Program of The Cooperative And Sme Office of East Java Province Through Bank MSMEs BPR Jombang Branch on The Income and Welfare of MSMEs - Megasari, Putri Agung; Sumarsono, Hadi; Sumanto, Agus (PT. EQUATOR SINAR AKADEMIA, 2025)
The problem of MSME fund capitalization is a serious problem and requires the right solution. One of the efforts of the government and stakeholders to accelerate sustainable economic recovery amid the Covid-19 pandemic and to increase the productivity of MSMEs is to expand access to financing through optimizing the distribution of revolving fund credit programs for micro, small and medium enterprises. This research is quantitative research. The research data is primary, namely the scale of the questionnaire for customers and secondary, namely data belonging to Dinkop-UKM. Data analysis techniques through descriptive analysis, effectiveness analysis and simple linear regression analysis. The results of this study are: 1) the effectiveness of the Dinkop-UKM revolving fund program through the Jombang branch of the MSMES BPR Bank affects the income of MSMEs, 2) the effectiveness of the Dinkop-UKM revolving fund program through the Jombang branch of the MSMES BPR Bank affects the improvement of MSME welfare, and 3) the income of MSMEs receiving Dinkop-UKM revolving funds through the Jombang branch of the MSMES BPR Bank affects the improvement of MSME welfare